Optimum time for collection of root samples for chromosome observation in yams (Dioscorea spp.) - Babil, P.K.; Kikuno, H.; Shiwachi, H.; Toyohara, H.; Fujigaki, J.; Fujimaki, H.; Asiedu, Robert (2010)
The genus Dioscorea is considered to be one of the most difficult groups for cyto-taxonomic studies because of the large number and small size of the chromosomes. The objective of the present study was to develop an efficient method of chromosome observation by identifying the optimum time for collecting root samples containing large numbers of metaphase cells. In the present investigation, two breeders’ lines developed at IITA, TDa 98/01183 (D. alata) and TDr 95/18544 (D. rotundata) which were identified as tetraploids (2n = 4x = 40) were used. To take samples for observation, root tips were collected from vine cuttings and seed tuber sets. In the root cells obtained from the seed tuber sets of both cultivars, TDa 98/01183 and TDr 95/18544, two peaks in the frequency of metaphase cells appeared in the diurnal cycle of cell division. The first peak was observed at seven hours after sunrise (1:00pm) and the second at 19 hours after sunrise (1:00am). In the roots of the seedlings obtained from vine cuttings, the first peak of frequency of metaphase cells appeared at four hours after sunrise (10:00am) in both cultivars and the second peak at 16 hours (10:00pm) in TDa 98/01183, but at 13 hours in TDr 95/18544 (7:00pm). Based on the results obtained, a cycle of cell division is considered to exhibit a periodicity of about 12 hours. The present investigation enabled to identify the optimum times for collecting root tip samples from rooted vine cuttings and seed tuber sets. The findings may facilitate cytogenetic studies in yams.